2011
DOI: 10.1371/journal.pntd.0001398
|View full text |Cite|
|
Sign up to set email alerts
|

Entamoeba lysyl-tRNA Synthetase Contains a Cytokine-Like Domain with Chemokine Activity towards Human Endothelial Cells

Abstract: Immunological pressure encountered by protozoan parasites drives the selection of strategies to modulate or avoid the immune responses of their hosts. Here we show that the parasite Entamoeba histolytica has evolved a chemokine that mimics the sequence, structure, and function of the human cytokine HsEMAPII (Homo sapiens endothelial monocyte activating polypeptide II). This Entamoeba EMAPII-like polypeptide (EELP) is translated as a domain attached to two different aminoacyl-tRNA synthetases (aaRS) that are ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…E. coli C41(DE3) cells were transformed with pET30-EhKRS vector [15]. The resulting recombinant protein harbors an amino-terminal hexahistidine tag and two additional residues from the cloning process (MHHHHHHML instead of the initial M).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 3 more Smart Citations
“…E. coli C41(DE3) cells were transformed with pET30-EhKRS vector [15]. The resulting recombinant protein harbors an amino-terminal hexahistidine tag and two additional residues from the cloning process (MHHHHHHML instead of the initial M).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…In the genus Entamoeba , lysyl‐ and methionyl‐tRNA synthetases (EhKRS and EhMRS) share a common C‐terminal domain of 166 amino acids. This domain is highly similar to the human endothelial monocyte activating polypeptide II (EMAPII), and was named Entamoeba EMAPII‐like polypeptide (EELP) [15]. Human EMAPII is an inflammatory cytokine that induces apoptosis and migration in endothelial cells [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that human tyrosyl-, tryptophanyl-, and lysyl-tRNA synthetases can be secreted extracellularly and can mimic cytokines (4,31,32). TyrRS of Plasmodium and LysRS of Entamoeba also mimic the functions of human cytokines (24,33).…”
Section: Discussionmentioning
confidence: 99%